Eksplorasi Konsep Diri para Pengguna TikTok dalam Memenuhi Social Needs pada Uses and Gratification Theory - Filza Alifah Hasny; Shavira Hanza Renadia; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
This qualitative study focuses on self-exploration of TikTok users in finding and creating educational content with fellow social network users. Researchers see the role of human needs psychologically and socially, which raises certain expectations from using TikTok and leads to fulfillment of needs. Researchers also saw the comparison of Gratification Sought (GS) with Gratification Obtained (GO) as the fulfillment of the needs sought to achieve the satisfaction desired by individuals in using TikTok. Researchers found that there were internal and external factors in self-exploration that influenced the fulfillment of the needs of using TikTok.